Whole‐Device Entanglement in a 65‐Qubit Superconducting Quantum Computer. Issue 10 (5th September 2021) - Mooney, Gary J.; White, Gregory A. L.; Hill, Charles D.; Hollenberg, Lloyd C. L.
Abstract: The ability to generate large‐scale entanglement is an important progenitor of quantum information processing capability in noisy intermediate‐scale quantum (NISQ) devices. In this paper, the extent to which entangled quantum states over large numbers of qubits can be prepared on current superconducting quantum devices is investigated. Native‐graph states on the IBM Quantum 65‐qubit ibmq_manhattan device and the 53‐qubit ibmq_rochester device are prepared and quantum readout‐error mitigation (QREM) is applied. Connected entanglement graphs spanning each of the full devices are detected, indicating bipartite entanglement over the whole of each device. The application of QREM is shown to increase the observed entanglement within all measurements, in particular, the detected number of entangled pairs of qubits found within ibmq_rochester increases from 31 to 56 of the total 58 connected pairs. The results of this work indicate full bipartite entanglement in two of the largest superconducting devices to date. Abstract : Entanglement plays an important role in fundamental physics and is a unique resource that is at the core of quantum computing. The extent of bipartite entanglement is investigated for graph states prepared on two of the largest IBM quantum superconducting devices of 53 and 65 qubits. The authors report successful generation of full bipartite entanglement on both devices.